Vigorous and moderate physical activity among overweight and obese adults in Malaysia: Sociodemographic correlates - Cheah, Yong Kang; Azahadi, Mohd Omar; Phang, Siew Nooi; Abd Manaf, Noor Hazilah (Elsevier B.V, 2019)
Background: This study examines the effects of sociodemographic factors on participation in vigorous and moderate physical activity and how they vary across bodyweight group (underweight, normal, overweight, obese I, obese II). Methods: This study uses a nationally representative data with a sample of 10141 respondents. Bivariate and multivariate analyses are stratified by bodyweight group. The intensity of physical activity is measured using metabolic equivalent (MET). Vigorous physical activity has >6 MET, while moderate physical activity has ≤6 MET.Results Several important findings are noteworthy. First, age has a positive impact on moderate physical activity among obese I individuals but a negative impact on moderate physical activity among obese II individuals. Second, education is significant in determining participation in all intensity levels of physical activity among obese I individuals. Third, higher income obese II individuals spend less time in vigorous physical activity than their lower income counterparts. However, higher income overweight and obese I individuals spend less time in moderate physical activity compared with those who have lower income. Fourth, overweight, obese I and obese II males spend more time in vigorous and total physical activity than their female counterparts, but they allocate less time for moderate physical activity.Conclusions It appears that sociodemographic factors play an important role in determining participation in vigorous and moderate physical activity among overweight and obese adults. We conclude by discussing implications for policies directed towards promoting physically active lifestyle among overweight and obese adults who are unlikely to spend time in physical activity.